2018
DOI: 10.1101/381228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fitness-Dependent Recombination Can Be Evolutionarily Advantageous in Diploids: a Deterministic Mutation–Selection–Balance Model

Abstract: Recombination's omnipresence in nature is one of the most intriguing problems in evolutionary biology. The question of why recombination exhibits certain general features is no less interesting than that of why it exists at all. One such feature is recombination's fitness dependence (FD). The so far developed population-genetics models have focused on the evolution of FD recombination mainly in haploids, although the empirical evidence for this phenomenon comes mostly from diploids. Using numerical analysis of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…At that, both the benefits and the costs are function of amplitude of RR plasticity. The interplay between these two function is not trivial, and the net function can be even nonmonotonous, so that an intermediate amplitude of RR plasticity sometimes appears optimal, as in our previous study [62]. The examined forms of CD recombination appeared to be favored over the corresponding optimal constant RR in different proportion of cases.…”
Section: The Evolutionary Advantage Of CD Recombination In the Hostmentioning
confidence: 50%
See 2 more Smart Citations
“…At that, both the benefits and the costs are function of amplitude of RR plasticity. The interplay between these two function is not trivial, and the net function can be even nonmonotonous, so that an intermediate amplitude of RR plasticity sometimes appears optimal, as in our previous study [62]. The examined forms of CD recombination appeared to be favored over the corresponding optimal constant RR in different proportion of cases.…”
Section: The Evolutionary Advantage Of CD Recombination In the Hostmentioning
confidence: 50%
“…We considered three forms of CD recombination: (i) parasite-dependent ID recombination were examined in the models with two and three selected loci, while FD recombination -only in the model with three selected loci. The reason is that FD recombination is imaginable only in the presence of variation in fitness among those genotypes in which recombination has fitness consequences in the next generation, which requires at least three selected loci [60,62].…”
Section: Recombination Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In diploids, the "abandon-ship" mechanism has been shown to be inefficient (Agrawal et al 2005). However, our recent simulations demonstrate that fitness-dependent recombination can evolve in diploids under certain scenarios, such as cyclical selection (Rybnikov et al 2017), Red Queen dynamics (Rybnikov et al 2018a), and mutation-selection balance (Rybnikov et al 2018b). In all our models, fitness-dependence was assumed only for recombination within the selected system.…”
Section: Evolvability Of Fitness Dependencementioning
confidence: 99%
“…This can make plastic recombination beneficial only if there is a variation in fitness among heterozygous genotypes, which requires at least three selected loci. Importantly, the evolutionary advantage/disadvantage of fitness-dependent recombination is determined by a trade-off between two opposite effects: benefits from protecting best allele combinations, and costs of shifting population mean recombination rate (Rybnikov et al 2018b). The cost often outbalances the benefits, which may be one of the reasons why some experimental-evolution studies reported no selection for recombination rate plasticity (Kerstes et al 2012;Kohl and Singh 2018).…”
Section: Evolvability Of Fitness Dependencementioning
confidence: 99%